2022
DOI: 10.1126/sciadv.abl9051
|View full text |Cite
|
Sign up to set email alerts
|

Premature aging in mice with error-prone protein synthesis

Abstract: The main source of error in gene expression is messenger RNA decoding by the ribosome. Translational accuracy has been suggested on a purely correlative basis to positively coincide with maximum possible life span among different rodent species, but causal evidence that translation errors accelerate aging in vivo and limit life span is lacking. We have now addressed this question experimentally by creating heterozygous knock-in mice that express the ribosomal ambiguity mutation RPS9 D95N, resulting in genome-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 62 publications
0
32
0
1
Order By: Relevance
“…There is currently no mouse model for NGPS but a recent study reported the effect of error- prone protein synthesis in mice ( 48 ). Through engineering a specific ribosomal mutation, the authors induced genome-wide translational errors in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is currently no mouse model for NGPS but a recent study reported the effect of error- prone protein synthesis in mice ( 48 ). Through engineering a specific ribosomal mutation, the authors induced genome-wide translational errors in mice.…”
Section: Discussionmentioning
confidence: 99%
“…( E ) Translation error rate measured as an increased read-through using a dual luciferase assay. G418 was used as a positive control for the induction of translational errors ( 48 ). Results are derived from the ratio hFluc/hRluc and given as fold induction.…”
Section: Fig S1mentioning
confidence: 99%
“…Therefore, the age-dependent enrichment of ribosome components might affect protein homeostasis and promote a loss of proteostasis, one of the primary hallmarks of aging. Indeed, flawed translation has been described to lead to premature aging (Shcherbakov et al 2022) and even promote early symptoms of Alzheimer’s disease in aging mice (Brilkova et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…to lead to premature aging (Shcherbakov et al 2022) and even promote early symptoms of Alzheimer's disease in aging mice (Brilkova et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced translational fidelity often leads to detrimental effects such as slow growth, cell death, and neurological disorders (30). Recent studies in yeasts, flies, worms, and mice also demonstrate that increasing translational fidelity by a ribosomal mutation improves the life span, whereas decreasing translational fidelity leads to accelerated aging (31,32). However, maintaining high fidelity also comes with costs, and increasing translational errors have been shown to be beneficial under certain conditions.…”
Section: Introductionmentioning
confidence: 99%